Effects of Carbonyl-cyanide m-chlorophenylhydrazone on Mitochondrial Function of H9C2 Cells - Yen, Ngo Thi Hai; Khanh, Bui Thi Van; Hien, Vu Thao; Thuy, To Thanh; Bich, Pham Thi; Trang, Dang Thi Ha; Thu, Vu Thi (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 33 No 2, 2017)
We examined the effects of carbonyl-cyanide m-chlorophenylhydrazone (CCCP) on mitochondrial function of H9C2 cells. Composition of mitochondrial membrane lipids (cardiolipin) and mitochondrial membrane potential was analyzed by fluorescence intensity change of tetramethl rhodamine ethyl ester (TMRE) and 10-nonyl acridine orange (NAO) using the LSM800 confocal microscope. Our results showed that CCCP strongly and simultaneously affected mitochondrial structure and function of H9C2 cells.